Electroimmunoassay of Plasma Subunits-A and -S in a Case of Congenital Fibrin Stabilizing Factor Deficiency - Barbui, T; Cartei, G; Chisesi, T; Dini, E (Thrombosis and Haemostasis, 1974)
Antigenic material related to the fibrin stabilizing factor (Factor XIII-FSF) has been found in all the examined patients with congenital deficiency, albeit in reduced amount.Recently, Bohn et al. (1973) and Israels et al. (1973) showed that plasma Factor- XIII is composed by two subunits, A (or a) and S (or b); the former active protein, the latter probably FSF-binding protein.Using specific anti-S and anti-A antisera the Authors found, in a case of congenital deficiency of factor XIII, absence of subunit A. Subunit S presented abnormal behaviour as demonstrated by means of quantitative immunoelectrophoresis according to Laurell.